Exploring Possible Futures of Transnational Cooperation of European Universities to Enhance Resilience - Claeys-Kulik, Anna-Lena; Jørgensen, Thomas (International Higher Education, 2024)
The article explores possible futures of transnational cooperation of European universities outlining drivers of change and four forecasts developed in the context of the European University Association’s project “Universities and the Future of Europe” (UniFE). It makes a pledge for using foresight and futures thinking in combination with strategic decision-making to enhance the resilience of universities in times of uncertainty and accelerated change.